2019
DOI: 10.1002/mc.22965
|View full text |Cite
|
Sign up to set email alerts
|

Camphor white oil induces tumor regression through cytotoxic T cell‐dependent mechanisms

Abstract: Bioactive derivatives from the camphor laurel tree, Cinnamomum camphora, are posited to exhibit chemopreventive properties but the efficacy and mechanism of these natural products are not fully understood. We tested an essential‐oil derivative, camphor white oil (CWO), for anti‐tumor activity in a mouse model of keratinocyte‐derived skin cancer. Daily topical treatment with CWO induced dramatic regression of pre‐malignant skin tumors and a two‐fold reduction in cutaneous squamous cell carcinomas. We next inves… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 63 publications
(147 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have also been reported that the essential oils of Curcuma rhizome and leaves induce apoptotic cell death in lung and liver cancer cells [ 42 , 43 ]. The cytotoxicity is attributed to the specific compounds such as α-phellandrene [ 44 , 45 ], camphor [ 46 ], curdione [ 47 , 48 ], eucalyptol [ 49 , 50 ], terpinolene [ 51 ], and α-pinene [ 52 , 53 ], which are already known to induce apoptosis and signaling interruption in cancer cell. The cytotoxic effect was mediated through cell cycle inhibition at the G 2 /S checkpoint [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also been reported that the essential oils of Curcuma rhizome and leaves induce apoptotic cell death in lung and liver cancer cells [ 42 , 43 ]. The cytotoxicity is attributed to the specific compounds such as α-phellandrene [ 44 , 45 ], camphor [ 46 ], curdione [ 47 , 48 ], eucalyptol [ 49 , 50 ], terpinolene [ 51 ], and α-pinene [ 52 , 53 ], which are already known to induce apoptosis and signaling interruption in cancer cell. The cytotoxic effect was mediated through cell cycle inhibition at the G 2 /S checkpoint [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…P. cylindraceus oil has been reported to provide the benefits of antimicrobial activity and medicinal value [ 49 ]. P. cylindraceus oil is dominated by monoterpenes; especially camphor and 1,8-cineol have extensive antibacterial potential because Gram-positive and Gram-negative bacteria were found susceptible to these oils [ 50 , 51 ]. The strong bactericidal effect of polymeric bionanocomposite may be attributed to TiO 2 nanoparticles that strongly bond with electron-donating groups in bioactive compounds containing oxygen, sulfur, and nitrogen.…”
Section: Resultsmentioning
confidence: 99%
“…Camphor has been reported to have anti-skin-aging effects as a cosmetic ingredient [ 17 ], anti-genotoxic effects at low concentrations [ 33 ], and antitumor activity [ 34 ]. In this study, we used camphorquinone (CQ), a camphor derivative that is widely used as a photoinitiator, to trigger the polymerization process during dental composite preparation [ 35 ].…”
Section: Discussionmentioning
confidence: 99%